Perceived Disagreement and Heterogeneity in Social Networks: Distinct Effects on Political Participation. Issue 2 (3rd March 2016) - Guidetti, Margherita; Cavazza, Nicoletta; Graziani, Anna Rita
ABSTRACT: Although the coexistence of conflicting opinions in society is the very core of democracy, people's tendency to avoid conflict could keep them away from political discussion and participation. On the other hand, being exposed to diverse political views could motivate citizens to participate. We conducted secondary analyses on two 2013 ITANES (Italian National Election Studies) probability samples in order to test the hypotheses that perceived network disagreement (between an individual and her/his discussion partners) and heterogeneity (among discussants holding different political opinions) exert independent and opposite effects on political participation through motivation and knowledge. Results converged in showing that disagreement dampened, while heterogeneity encouraged, political participation (voting, propensity to abstain in future, offline and online activism, and timing of vote decision) by decreasing or increasing, respectively, political interest and, in turn, knowledge.